Development of Arabic Language Learning Media Using the Doratoon Application in Improving Speaking Skills : Pengembangan Media Pembelajaran Bahasa Arab Menggunakan Aplikasi Doratoon dalam Meningkatkan Keterampilan Berbicara - Moh. Zulkifli Paputungan; Ceysi Yuliana Hasan; Miatin Rachmawati; M. Kholis Amrullah (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Arabic learning is learning that requires components as tools to help students understand the material being taught. These components are like learning media. However, at MTs al-Khairat Gorontalo City, especially grade VII, in the process of learning Arabic, learning media has not been used. Thus, students get bored quickly and the learning outcomes are not optimal. Purpose: This study aims to develop animation-based Arabic learning media using the Doratoon application to increase the learning interest of grade VII students of MTs Al-Khairat Gorontalo City. Methods: The method used is Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, and evaluation). Results and Discussion: The results of this media development show that the Doratoon application is effective in improving students' speaking skills. This is measured at a figure that reaches 93% Based on the validity test of the first two 2 validators, the calculation results show that the average score reaches 89%, which is included in the category of interpretation of the interval of 80% - 100%, with a rating of "Very Feasible". This indicates that according to the material expert validator, the developed product has met the excellent eligibility criteria and can be used effectively. The second validator as a media expert in the evaluation results showed that the media obtained a score of 56 out of a total of 60, with a percentage of 93%, which indicates the category of "Excellent". This media has an attractive appearance, good color harmony, and effective layout arrangements, and fulfills learning objectives well. Conclusion and Implications: The use of animation video-based learning media using the Doratoon application has been proven to be effective in increasing students' motivation and understanding of Arabic material at MTs Al-Khairat, Gorontalo City. Based on the results of the implementation and evaluation, the majority of students showed a positive response to the developed media, with an average score of 89%, which is included in the "Good" category. While there are some students who are still struggling, efforts to adjust learning strategies and pay more attention to those students can improve future outcomes. In addition, the development of this media also contributes to improving the quality of Arabic teaching, especially in creating a learning atmosphere that is more interactive, interesting, and in accordance with the needs of the current digital generation.